SELECTION OF EXTRACURRICULAR ACTIVITIES IN SMK INSAN AQILAH 4 JAKARTA USING PROFILE MATCHING METHOD - Wahyudin, Wahyudin; Saryoko, Andi; Aziz, Abdul; Nurmalia, Lia (Jurnal Pilar Nusa Mandiri, 2020)
This research is based on the observations and experiences of researchers, because the many extracurricular activities in schools make it difficult for students to determine extracurricular activities that can develop their personality, talents, and abilities outside the academic field, therefore the system is created to select extracurricular activities. The aim is to help students deal with extracurricular selection problems. The application of the Profile Matching method in the decision support system for the selection of extracurricular activities is expected to help provide recommendations for extracurricular activities to overcome the problem of selecting extracurricular activities and can facilitate students in selecting extracurricular activities.